The fourth instar larva and pupa of the Neotropical biting midge Forcipomyia (Forcipomyia) rioplatensis Marino and Spinelli (Diptera: Ceratopogonidae) - Spinelli, Gustavo Ricardo (2005)
he fourth instar larva and pupa of the Neotropical biting midge, Forcipomyia (Forcipomyin) rioplntensis Marino and Spinelli, are described and illustrated using phase-contrast and scanning electron microscopes. Larvae, pupae and adults of Forcipomyin rioplatensis were collected from nests of the monk parakeet, Myiopsittcl rnonnchus monnchrrs (Boddaert), in San Vicente, Buenos Aires Province, Argentina. Larvae have character states typical of other species of Forcipomyin with herbivorous ceratopogonid larvae. This species is compared with its very similar Nearctic congener, Forcipomyin (F.) bipunctatrapropinqua Chan and LeRoux.